Social Cognition and Interaction Training (SCIT) versus Training in Affect Recognition (TAR) in patients with schizophrenia: A randomized controlled trial. (October 2021) - Lahera, G.; Reboreda, A.; Vallespí, A.; Vidal, C.; López, V.; Aznar, A.; Fernández, P.; Escolar, M.; Martínez-Alés, G.; Rodriguez-Jimenez, R.; Halverson, T.; Frommann, N.; et al.
Abstract: Introduction: Training in Affect Recognition (TAR) is a "targeted" and computer-aided program that has been shown to effectively attenuate facial affect recognition deficits and improve social functioning in patients with schizophrenia. Social Cognition and Interaction Training (SCIT) is a group "broad-based" intervention, that has also been shown to improve emotion recognition, theory of mind (ToM), and social functioning. To date, no study has compared the efficacy of two different social cognitive interventions. Objectives: We aim to compare the efficacy of TAR and SCIT on schizophrenia patients' performance on facial affect recognition, theory of mind, attributional style and social functioning before, after treatment, and three months thereafter. Methods: One hundred outpatients with a diagnosis of schizophrenia were randomly assigned to the TAR or SCIT condition and completed pre- (T0) and posttreatment (T1) assessments and a 3-month follow up (T2) of emotion recognition (ER-40), theory of mind (Hinting Task), attributional style (AIHQ) and social functioning (PSP). Results: The entire sample, receiving TAR or SCIT, showed improvements in theory of mind, attributional style, clinical symptoms and social functioning. This effect was maintained at three-months. The TAR intervention was more efficacious than the SCIT program in improving the recognition of facial emotions (ER-40). The TAR intervention also demonstrated a lower drop-out rate than the SCIT intervention. Conclusions: There were improvements in social cognition, symptomatology and functioning of patients in the entire sample, receiving SCIT or TAR. Both TAR and SCIT appear as valuable treatments for people with schizophrenia and social cognitive deficits.